Enhanced Weathering and Erosion of a Cohesive Shore Platform Following the Experimental Removal of Mussels - Gonzalez, Juliana A.; Coombes, Martin A.; Palomo, M. Gabriela; Isla, Federico I.; Soria, Sabrina A.; Gutiérrez, Jorge L. (Frontiers in Marine Science, 2021)
The organisms inhabiting intertidal platforms can affect their weathering and erosion rates. Research on biotic influences on platform integrity has traditionally emphasized the role of bioeroders (i.e., organisms that scrap or bore into platforms via mechanical and chemical means). Yet, recent studies illustrate that covers of sessile organisms on the surfaces of intertidal platforms can have bioprotective effects by reducing the efficacy of physical weathering and erosion agents. Eroding cliffs fronted by cohesive shore platforms are a pervasive feature along the continental Argentinean coastline (37–52°S). In this study, we investigated how mussel (Brachidontes rodriguezii) cover mediates weathering and erosion of a cohesive, consolidated silt platform at Playa Copacabana (5 km north of Miramar, Buenos Aires Province; 38° 14′ S, 57° 46′ W). By means of mussel removal experiments, we found that mussel cover attenuates variations in platform surface temperatures, enhances moisture retention during low tide, reduces rates of salt crystallization within the pores of the platform material, and attenuates hydrodynamic forcing on the platform surface. Mussel removal also led to a 10% decrease in surface hardness and a 2-mm reduction in platform height after 5 months. Collectively, our findings indicate that mussel beds limit substrate breakdown via heating-cooling, wetting-drying, and salt crystallization and provide some of the first experimental field evidence for the direct impacts of biotic cover on platform erosion. As intertidal platforms protect the cliffs behind from the hydraulic impact of waves, which may be enhanced with future sea-level rise, we posit that the protection of platforms by mussels indirectly moderates coastline retreat, especially on soft cohesive shores.